Comunicación Política: Campaña electoral de Mauricio Rodas a la alcaldía de Quito. - Acuña Coloma, Josue Roberto (2015)
The media in a hyper-connected society play an important role in the development of political processes, is why political communication emerges as a discipline that is responsible for the distribution, production and analysis of news content through various elements such marketing and propaganda. Mauricio Rodas triumph in the elections for mayor of Quito, is the sign of the use of political marketing strategies, some of which were based on errors candidate campaign adversary so I got a good result. So in this research conduct an approach to the main concepts of communication, marketing, sociology and politics .For to know how communication strategies and policies are structured in a particular time as in the case of an election campaign. The goal is to publicize the importance of Political Communication in the local electoral situation. As this is a relatively new field of study, it is necessary to know the role of the media, politicians and citizens in a context where every time there is a greater presence of social networks as active channels to generate public opinion.